Li-Mg/Sba-15 Catalyst For Selective Etherification Of Glycerol To Diglycerol - Admiral, Afrizal (2013)
Drastic increase in crude glycerol production promises a great opportunity for researchers to use it as a renewable feedstock to produce beneficial products. Etherification of glycerol to polyglycerols using heterogeneous base catalysts has been studied intensively over the past few years but in-depth understanding on the process is yet to be achieved. Mesoporous silicas are the most promising ones among all catalyst supports due to their unique characteristics of high thermal stability, large surface area and present no limitation when dealing with large molecules. The primary aim of this study was to prepare heterogeneous base catalysts for the etherification of glycerol to polyglycerols. SBA-15 was successfully synthesized and it exhibited large pore volume, high surface area and good structural ordering with narrow pore size distribution. The catalysts were prepared by impregnating active metals (Li, Mg and Cs) into the SBA-15. The catalyst materials were subjected to the surface analysis, X-ray diffraction analysis, transmission electron microscope (TEM), scanning electron microscope (SEM) and Hammett basic strength test. 5 wt. % of lithium and cesium could result in partial structural collapse of SBA-15. Binary impregnation of SBA-15 with magnesium followed by the most active metal i.e. lithium could preserve the mesoporous structure. Magnesium acted as a coating layer to preserve SBA-15 framework as well to enhance dispersion of lithium.